Politik Asosiasi dalam Pendidikan Kolonial untuk Membangun Elit Pribumi Pro-Kolonial - Firhan Miftahul Aziz (Forum for Social and Humanities Studies, 2025)
This article aims to critically examine the implementation of association politics in the field of education during the Dutch colonial period and its impact on Indonesian society, especially in shaping the social structure and mindset of the educated generation. By tracing the basic concept of association politics as a strategy of power wrapped in a narrative of cooperation and modernization, this article shows that colonial education was not a neutral means to educate the nation, but rather a hegemonic tool that subtly created a native elite loyal to the colonial government. Although this system was initially intended to strengthen Dutch domination, paradoxically, it also opened up space for the growth of national awareness and a spirit of resistance among the educated. Therefore, this article concludes that association politics in education reflects the ambivalence of colonialism which on the one hand oppresses and limits, but on the other hand unknowingly also provides the seeds of liberation that later became the foundation of the Indonesian independence struggle.